2016
DOI: 10.1137/16m1067494
|View full text |Cite
|
Sign up to set email alerts
|

Wasserstein Loss for Image Synthesis and Restoration

Abstract: This paper presents a novel variational approach to impose statistical constraints to the output of both image generation (to perform typically texture synthesis) and image restoration (for instance to achieve denoising and super-resolution) methods. The empirical distributions of linear or non-linear descriptors are imposed to be close to some input distributions by minimizing a Wasserstein loss, i.e. the optimal transport distance between the distributions. We advocate the use of a Wasserstein distance becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 63 publications
0
24
0
Order By: Relevance
“…Several tools from optimal transport (OT) have already been applied to texture synthesis: Rabin et al [20] and Xia et al [25] formulate texture mixing via Wasserstein barycenters, Tartavel et al [21] use Wasserstein distances in a variational formulation of texture synthesis, and Gutierrez et al [9] apply discrete OT in order to specify a global patch distribution. Here, we suggest to locally apply a semi-discrete transport plan which can be seen as a tweaked nearest-neighbor projection.…”
Section: Introductionmentioning
confidence: 99%
“…Several tools from optimal transport (OT) have already been applied to texture synthesis: Rabin et al [20] and Xia et al [25] formulate texture mixing via Wasserstein barycenters, Tartavel et al [21] use Wasserstein distances in a variational formulation of texture synthesis, and Gutierrez et al [9] apply discrete OT in order to specify a global patch distribution. Here, we suggest to locally apply a semi-discrete transport plan which can be seen as a tweaked nearest-neighbor projection.…”
Section: Introductionmentioning
confidence: 99%
“…Wasserstein barycenters were used in [55,67] to address texture mixing. Tartavel et al [60] extended variational texture synthesis by combining discrete OT distances computed on several (non-linear) filter responses. Finally, Gutierrez et al [21] proposed a texture synthesis method that enforces the patch distribution at multiple scales by applying a discrete OT plan.…”
Section: Global Statistical Controlmentioning
confidence: 99%
“…Recently, an approach has been proposed in [8,9], which introduces a preliminary step of dictionary learning for exploiting the given patch, and (not least) the Wasserstein distance for comparing the histograms of the entire texture with an extended version of the small patch. While the Wasserstein distance is well-known in image processing and computer vision under the name "earth mover distance" [10], it was only recently expanded to the context of texture synthesis [11,9,12]. Under the assumption that the main texture characteristics are contained in their Fourier magnitude [13], many works have shown that an efficient synthesis method is achieved when the texture phase is randomized [7,9].…”
Section: Related Workmentioning
confidence: 99%
“…Hence, we replicate the patch v so as to obtain a larger imageṽ ∈ R N such that the normalized histogram νṽ is equal to ν v . Although the Wasserstein distance is nonconvex (due to the histogram transformation), its gradient is Lipschitz-continuous and takes the following form [8,12]…”
Section: Statistical Priormentioning
confidence: 99%